The Development of Preparedness Board Game as A Learning Media for Natural Disaster - Sri Adelila Sari; Sri Wahyuni (Syiah Kuala University, 2015)
This study was aimed to develop the preparedness board game for natural disaster. The method used was research and development (R D) with ADDIE model which was included five steps, i.e., (i) Analyses, (ii) Design, (iii) Development, (iv) Implementation, and (v) Evaluation. Samples of this study were students of grade VI in MIN Ulee Kareng, Banda Aceh, Indonesia. The quality of the board game was based on the validation results. The validation aspects included were (i) media format, (ii) visual aspects, (iii) media function, and (iv) the clarity of the concepts. Due to the validation aspects, therefore the validation of developed board game were found to be 97.2; 91.7; 88.9; and 100.9 percents, respectively. The results of this study indicated that developed preparedness board game was worth based characteristics of students. Meanwhile, the average assessment of the feasibility assessment aspects of the media was found to be 94.4 percent, which could be decided to very good. It was concluded that learning media preparedness board game could be used in the learning process in the natural disaster material.